Digital Intervention for Students with Learning Disabilities - Maulana Arif Muhibbin (Analitika: Jurnal Magister Psikologi UMA, 2020)
The Systematic Literatur Review aims to reveal kinds of assistive technology that applied to students with a learning disability (LD) in several articles selected through the screening process in 2015-2020. The review was conducted on three online databases, they are ScienceDirect, Sage Journal dan Proquest. There were 7 articles reviewed from a total of 32 obtained from screening inclusion and exclusion criteria. Based on the analysis of several studies revealed that using digital intervention such as Smartpen, PC, and Smartphone which has had appropriate application, have supported and increased the performance of students with learning disabilities in the area of learning skills. The development of specific digital intervention on students with learning disabilities needs to be applied in future research.